2020
DOI: 10.1017/s1049023x20000485
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing End-Tidal Carbon Dioxide to Diagnose Diabetic Ketoacidosis in Prehospital Patients with Hyperglycemia

Abstract: Background:Early identification of diabetic ketoacidosis (DKA) may improve clinical outcomes. Prior studies suggest exhaled end tidal carbon dioxide (ETCO2) provides a non-invasive, real-time method to screen for DKA in the emergency department (ED).Methods:This a retrospective cohort study among patients who activated Emergency Medical Services (EMS) during a one-year period. Initial out-of-hospital vital signs documented by EMS personnel, including ETCO2 and first recorded blood glucose level (BGL), as well … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 15 publications
2
3
0
Order By: Relevance
“…The positive and negative predictive values were 96.4% and 85.0% with an accuracy of 92.7%. The compelling predictive value of capnography in detecting diabetic ketoacidosis (DKA), as observed not only in this study but also in prior studies[ 5 6 7 8 9 10 ], strongly suggests the inclusion of end-tidal carbon dioxide (EtCO2) measurements in the diagnostic criteria for DKA.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The positive and negative predictive values were 96.4% and 85.0% with an accuracy of 92.7%. The compelling predictive value of capnography in detecting diabetic ketoacidosis (DKA), as observed not only in this study but also in prior studies[ 5 6 7 8 9 10 ], strongly suggests the inclusion of end-tidal carbon dioxide (EtCO2) measurements in the diagnostic criteria for DKA.…”
Section: Discussionsupporting
confidence: 76%
“…While numerous studies have explored the association of metabolic acidosis with capnography, most have targeted the pediatric population or had small sample sizes. [ 8 9 10 11 ] The present study, in contrast, recruited all its participants from the adult population and had a comparatively large sample size. The study assessed three possible roles of EtCO 2 : (a) its role as a triage tool for excluding DKA; (b) as an additional diagnostic criterion for DKA; and (c) its role in monitoring the treatment (degree of acidosis).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, it was concluded that there was a significant correlation between EtCO2 and bicarbonate (P<0.05). Similarly, previous studies have reported a significant linear correlation between end-tidal CO2 and bicarbonate [20][21][22]. As low bicarbonate level explains the metabolic acidosis present in patients with DKA, the linear significant correlation found between EtCO2 and bicarbonate is another result supporting that EtCO2 measurement can be used for diagnostic purposes in these patients.…”
Section: Discussionsupporting
confidence: 71%
“…[7][8][9][10][11] It has a significant association with lactate and anion gap elevation and has found to be an indicator of DKA in pediatric and adult populations. [12][13][14][15][16][17] Furthermore, numerous studies have shown ETCO 2 to have a strong association with acute disease severity and mortality in sepsis, trauma, and shock. 7,13,[18][19][20][21][22][23][24][25][26] Prior studies have explored the clinical utility of adding ETCO 2 to the initial triage assessment of patients.…”
Section: Introductionmentioning
confidence: 99%
“…It has been widely accepted as the criterion standard for confirming proper endotracheal tube placement and as a useful prognostic indicator of initial outcome of resuscitation in cardiopulmonary arrest 7–11 . It has a significant association with lactate and anion gap elevation and has found to be an indicator of DKA in pediatric and adult populations 12–17 . Furthermore, numerous studies have shown ETCO 2 to have a strong association with acute disease severity and mortality in sepsis, trauma, and shock 7,13,18–26 .…”
Section: Introductionmentioning
confidence: 99%